LA INFLUENCIA DEL CONTROL SOCIAL INFORMAL EN EL SISTEMA DE ADMINISTRACIÓN DE JUSTICIA - Buri Remache, Mercy Lissbeth (2024)
The present work entitled: “THE INFLUENCE OF INFORMAL SOCIAL CONTROL IN THE JUSTICE ADMINISTRATION SYSTEM”, exhibits the results of an investigation that demonstrates the existence of violation of constitutional rights of the prosecuted persons, in the guarantee of due process in the guarantee to be tried and punished by an impartial and competent judge within a criminal process; Furthermore, the results of the investigation show us the subjective contamination in the healthy criticism of the judge who has under his knowledge media criminal procedures that have caused shock in society. The Constitution of the Republic of Ecuador in Art. 76 exposes the constitutional rights, in the guarantee of due process, that all people have in all proceedings, among which, we find the right to the “presumption of innocence,” “be judged by an impartial judge”, etc.; However, according to the analysis carried out in this research, we can verify that these rights are violated, especially when a criminis news causes social commotion, its impact is so strong that citizens themselves make conjectures, issue value judgments, even Without knowing the procedural and/or real truth, they socially condemn the person who enjoys the presumption of innocence and who allegedly adapted his conduct to a criminal type provided for in the Comprehensive Organic Penal Code. On the other hand, we find that the media directly influences the creation of public opinion, managing to induce and influence society in general and those people who have the arduous job of administering justice, interfering in the logic and rationality of the healthy criticism. From the above, our work ends with the formulation of guidelines and purposes based on international regulations, with the purpose of solving the problem raised within the judicial system, which consists of applying the principle of "Judicial Reserve" in those criminal processes whose scenario is formed under the scheme of “a media process”; Consequently, suggest to the National Secretariat of Communication of Ecuador, as the regulatory body of the media and public opposition, greater control of the 5 information issued so that there is greater responsibility and empathy for the media to broadcast news; without leading to a violation of freedom of expression.